Pengaruh Peran Kepala Sekolah Sebagai Manajer, Komitmen Guru dan Motivasi Serta Etos Kerja Guru terhadap Peningkatan Kinerja Guru di SMA Negeri 2 Kuta Selatan - Desak Afriani; I Made Yudana; Dewa Gede Hendra Divayana (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine how much influence both separately and simultaneously the role of the principal as a manager, teacher commitment and motivation and teacher work ethic on improving teacher performance in SMA Negeri 2 Kuta Selatan. Data analysis used in this study is product moment correlation, partial correlation and multiple regression. Based on the research that has been done, it is concluded that: 1) there is a significant influence of the role of the principal as a manager on teacher performance with a product moment ry1 correlation coefficient = 0.678; ry1-2,3,4 = 0.320 and effective contribution = 14.60%; 2) there is a significant influence of teacher commitment on teacher performance with a product moment ry2 correlation coefficient = 0.788; ry2-1,3,4 = 0.319 and effective contribution = 21.20%; 3) there is a significant effect of work motivation on teacher performance with a product moment ry3 correlation coefficient = 0.780; ry3-1,2,4 = 0.315 and effective contribution = 20.70%; 4) there is a significant effect of work ethic on teacher performance with a product moment ry4 correlation coefficient = 0.772; ry4-1,2,3 = 0.320 and effective contribution = 20.70%; and 5) there is a simultaneous significant influence on the role of the principal as a manager, teacher commitment and work motivation and work ethic on teacher performance with product moment correlation coefficient values ry1,2,3,4 = 0.878 with multiple correlation coefficients (Ry1,2, 3.4)2 = 0.772 and an effective contribution of 77.2%.